EUFEMISME DALAM BAHASA POLITIK INDONESIA: KAJIAN KONSEPTUAL - Isnandi Abdul Rozak Riaji; Ahmad Zaelani; Rifdi Fahrizal Taharas (STISIP Widyapuri Mandiri, 2026)
This study discusses euphemisms in Indonesian political language as a linguistic strategy and instrument of power. Using a qualitative method based on literature review, the analysis was conducted using Allan & Burridge's theoretical framework, Fairclough's critical discourse analysis, and Orwell's reflections on political language. Data were obtained from political texts, mass media, official documents, and relevant academic literature. The results show that euphemisms are used to obscure reality and reduce public resistance. Terms such as “fuel price adjustment,” “organizational downsizing,” or “measured decisive action” demonstrate how language is used to frame perceptions and legitimize policies. From Allan & Burridge's perspective, euphemisms can be divided into political correctness and concealment. Fairclough's analysis confirms that this kind of language is reproduced by the media to form a discourse hegemony, while Orwell's reflections show the danger when lies are made to sound honest and oppression seems reasonable. In conclusion, political euphemisms in Indonesia are not only a linguistic phenomenon but also a socio-political practice that has implications for transparency, accountability, and the quality of democracy. Therefore, critical awareness is needed to read the hidden meanings behind political terms and to present a more honest counter-discourse.